The immunologically high-risk kidney recipient in the early post-COVID-19 period. To do or not to do? A case report - Antal, Oana; Daciana Elec, Alina; Muntean, Adriana; Moisoiu, Tudor; Melinte, Razvan Marian; Elec, Florin Ioan (Frontiers in Medicine, 2023)
Abstract Kidney transplantation is nowadays the treatment of choice for end-stage kidney disease (ESKD), and it is the most performed organ transplantation. During the COVID-19 pandemic, kidney-transplant recipients appeared to be at higher risk of morbidity and mortality due to severe forms of illness. The result was a decrease in the number of solid organs transplants worldwide, with patients’ reduced chance of receiving transplants. The best timing for surgery after COVID-19 infection is still controversial since most of the available data come from study periods with zero or low prevalence of vaccination and COVID-19 variants with high mortality rates. The American Society of Anesthesiologists (ASA) and the Anesthesia Patient Safety Foundation (APSF) Joint Statement on Elective Surgery/Procedures and Anesthesia for Patients after COVID-19 Infection states that elective surgery should be delayed for seven weeks after a SARS-CoV-2 infection in unvaccinated patients while making no clear statement for vaccinated ones, or those which have already been infected with the virus . Kidney transplant, as opposed to tissue transplant, is not an elective surgery, so the question raised is whether to do it or not. We present the case of a hyper-immunized 47-year-old male patient with end-stage chronic kidney disease who received a second kidney transplant, despite having a mild SARS-COV 2 infection just two weeks before his transplantation surgery.